Factors Associated with Depression and Generalized Anxiety Disorder in Antenatal Period - Muneeza Abdul Haleem, Samra Mobeen, Saima Jabeen, Mariam Malik, Ayesha Khan, Tahami Dar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Depression and generalized anxiety disorder (GAD) are among the most prevalent psychiatric conditions affecting women during the antenatal period. These mental health issues not only compromise maternal well-being but are also associated with adverse obstetric outcomes, including preterm birth, low birth weight, and impaired neonatal development. Despite the high burden in low- and middle-income countries, antenatal mental health often remains underdiagnosed and underreported. Objective: To determine the prevalence of depression and generalized anxiety disorder during pregnancy and to identify the associated sociodemographic and obstetric risk factors. Methods: A total of 200 pregnant women meeting the inclusion criteria were recruited. Data were collected using a validated Urdu version of the Hospital Anxiety and Depression Scale (HADS). Participants were informed about the study and consent was obtained before questionnaire administration. Sociodemographic, obstetric, and psychosocial variables were recorded. Data were analyzed using SPSS version 23. Descriptive statistics were computed, and logistic regression analysis was performed to determine associations between independent variables and outcomes. A p-value <0.05 was considered statistically significant. Results: The prevalence of antenatal depression and GAD was found to be 36.5% and 28.0%, respectively. Significant associations were observed between depression and unplanned pregnancy (p=0.002), low socioeconomic status (p=0.001), and lack of spousal support (p=0.004). Similarly, GAD was significantly associated with a history of miscarriage (p=0.008), presence of obstetric complications (p=0.010), and domestic stress (p=0.001). Conclusion: Depression and GAD are highly prevalent among antenatal women, with significant associations to modifiable social and obstetric risk factors. Routine screening during antenatal visits and targeted psychosocial support interventions could play a pivotal role in reducing maternal psychological morbidity and improving pregnancy outcomes. Keywords: Antenatal depression, Generalized anxiety disorder, Pregnancy, Risk factors, Maternal health